Newborn screening for abnormal haemoglobins in Jamaica: Practical issues in an island programme. (December 2022) - Serjeant, Graham R; Serjeant, Beryl E; Mason, Karlene P; Gibson, Felicea; Gardner, Ruth-Ann; Warren, Lansford; Hambleton, Ian R; Thein, Swee L; Happich, Margit; Kulozik, Andreas E
Objective: To report the diagnostic challenges of newborn screening for abnormal haemoglobins. Setting: Cord blood samples from 13 hospitals in southwest Jamaica taken in 2008–2019. Methods: Blood spots, collected from the umbilical cord, were analysed by high pressure liquid chromatography (HPLC) to reveal phenotypes for HbSS and HbCC, but genotype confirmation may require parental studies or gene sequencing. Such cases that were successfully traced were analysed in this follow-up study. Results: HPLC screening of 121, 306 samples detected HbAS in 11, 846 (9.8%), HbAC in 4508 (3.7%) and other electrophoretic abnormalities in 1090 babies. Among 101 previously unconfirmed cases, 34/90 (38%) with HPLC evidence of a HbSS phenotype had other genotypes, and 7/11 (64%) with a HbCC phenotype had other genotypes. Syndromes from the interaction of β thalassaemia occurred in 112 babies (85 with HbS, 27 with HbC) and of genes for hereditary persistence of fetal haemoglobin (HPFH) in 18 (12 with HbS, 6 with HbC). Variants other than HbS and HbC occurred in 270 babies, 16 in combination with either HbS or HbC, and 254 as traits. Most variants are benign even when inherited with HbS, although HbO Arab, HbD Punjab, or Hb Lepore Washington, which occurred in 6 cases, may cause sickle cell disease. Conclusions: Genes for β thalassaemia and HPFH are common in western Jamaica and when associated with HbS may present diagnostic challenges in newborns, as HbF and HbA2 have not reached diagnostic levels. Family and DNA studies may be necessary for genotype confirmation.